2022
DOI: 10.3390/molecules27227680
|View full text |Cite
|
Sign up to set email alerts
|

Thiolated Janus Silsesquioxane Tetrapod: New Precursors for Functional Materials

Abstract: Herein, we report synthetic strategies for the development of a bifunctional Janus T4 tetrapod (Janus ring), in which the orthogonal silsesquioxane and organic faces are independently functionalized. An all-cis T4 tetrasilanolate was functionalized to introduce thiol moieties on the silsesquioxane face and naphthyl groups on the organic face to introduce luminescent and self-organization properties. The stepwise synthesis conditions required to prepare such perfectly defined oligomers via a suite of well-defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Of particular interest is the use of cyclic compounds such as calixarenes and cyclotriphosphazenes since it allows one to control the amount of fluorophores and the geometry of the molecular system. It has been previously shown that cyclic siloxanes are convenient matrices for grafting chromophores and obtaining multichromophoric systems with controlled nanoscale architecture and properties. In particular, such an approach can be effective for obtaining intramolecular excimers and multimers. , The use of stereoregular cyclosiloxanes make it possible to arrange several chromophores in the same plane at a close distance, thus promoting the interfluorophore π–π interaction and the formation of excimers in an excited state . Along with the above, the close location of several chromophores opens up the possibility of obtaining π–π stacked self-assemblies of dye molecules, namely H-type aggregates, which possess unique optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest is the use of cyclic compounds such as calixarenes and cyclotriphosphazenes since it allows one to control the amount of fluorophores and the geometry of the molecular system. It has been previously shown that cyclic siloxanes are convenient matrices for grafting chromophores and obtaining multichromophoric systems with controlled nanoscale architecture and properties. In particular, such an approach can be effective for obtaining intramolecular excimers and multimers. , The use of stereoregular cyclosiloxanes make it possible to arrange several chromophores in the same plane at a close distance, thus promoting the interfluorophore π–π interaction and the formation of excimers in an excited state . Along with the above, the close location of several chromophores opens up the possibility of obtaining π–π stacked self-assemblies of dye molecules, namely H-type aggregates, which possess unique optical properties.…”
Section: Introductionmentioning
confidence: 99%